In-situ coating of leather with conducting polyaniline in colloidal dispersion mode - Ngwabebhoh, Fahanwi Asabuwa; Zandraa, Oyunchimeg; Sáha, Tomáš; Stejskal, Jaroslav; Trchová, Miroslava; Kopecký, Dušan; Pfleger, Jiří; Prokeš, Jan (Synthetic metals, 2022)
Four different leathers and a nonwoven fibrous mat have been coated with a conducting polymer, polyaniline, in situ during the oxidation of aniline hydrochloride in the presence of poly(N-vinylpyrrolidone) stabilizer. This colloidal dispersion approach prevented the undesirable formation of free polyaniline precipitate outside the leather fibers. The molecular structure of polypeptide fibers with deposited polyaniline is discussed on the basis of FTIR spectra. Raman spectroscopy confirmed that individual fibers were coated with a conducting polymer. The cross-sectional optical microscopy revealed that the leather was coated on both sides. The layer thickness, tens to hundreds micrometers, was determined by the penetration depth of reaction mixture. In the case of diabetic insole mat gambrela, polyaniline penetrated throughout the sample body. This was also confirmed by the measurement of transversal resistance. The typical sheet resistance was in units to hundreds kΩ/sq and differed but was of the same order of magnitude on top and bottom sides. The samples were subject to cyclic bending and of the resistivity changes have been monitored. Antibacterial activity of some leathers improved after the coating with polyaniline. [Display omitted] •The samples of leather were coated with a conducting polymer.•Polyaniline was deposited in-situ using a colloidal dispersion mode.•Various modes of electrical resistance determination are provided.•A new method testing the resistance changes upon cyclic bending was developed.•The applications of conducting leather composites are proposed.